Carnosine metabolism in diabetes is altered by reactive metabolites - Peters, Verena; Lanthaler, Barbara; Amberger, Albert; Fleming, Thomas; Forsberg, Elisabete; Hecker, Markus; Wagner, Andreas H.; Yue, Wyatt W.; Hoffmann, Georg F.; Nawroth, Peter Paul; Zschocke, Johannes; Schmitt, Claus P. (Amino acids, 2015)
Carnosinase 1 (CN1) contributes to diabetic nephropathy by cleaving histidine-dipeptides which scavenge reactive oxygen and carbonyl species and increase nitric oxide (NO) production. In diabetic mice renal CN1 activity is increased, the regulatory mechanisms are unknown. We therefore analysed the in vitro and in vivo regulation of CN1 activity using recombinant and human CN1, and the db/db mouse model of diabetes. Glucose, leptin and insulin did not modify recombinant and human CN1 activity in vitro, glucose did not alter renal CN1 activity of WT or db/db mice ex vivo. Reactive metabolite methylglyoxal and Fenton reagent carbonylated recombinant CN1 and doubled CN1 efficiency. NO S-nitrosylated CN1 and decreased CN1 efficiency for carnosine by 70 % (p < 0.01), but not for anserine. Both CN1 cysteine residues were nitrosylated, the cysteine at position 102 but not at position 229 regulated CN1 activities. In db/db mice, renal CN1 mRNA and protein levels were similar as in non-diabetic controls, CN1 efficiency 1.9 and 1.6 fold higher for carnosine and anserine. Renal carbonyl stress was strongly increased and NO production halved, CN1 highly carbonylated and less S-nitrosylated compared to WT mice. GSH and NO2/3 concentrations were reduced and inversely related with carnosine degradation rate (r = −0.82/−0.85). Thus, reactive metabolites of diabetes upregulate CN1 activity by post-translational modifications, and thus decrease the availability of reactive metabolite-scavenging histidine dipeptides in the kidney in a positive feedback loop. Interference with this vicious circle may represent a new therapeutic target for mitigation of DN.